A molecular and morphological reinvestigation of topotype specimens of Calliblepharis occidentalis (Cystocloniaceae, Rhodophyta). Issue 2 (4th March 2019) - Soares, Luanda Pereira; Toyota Fujii, Mutue; Díaz-Tapia, Pilar; Hommersand, Max H.
ABSTRACT: Calliblepharis occidentalis was originally described from northeastern Brazil and later reduced to synonymy with C. fimbriata from South Africa. It was later reinstated, but phylogenetic relationships with other congeners and several morphological characters remain poorly understood. In the present article, topotype specimens of C. occidentalis were reinvestigated using molecular, morphological and anatomical data, and its phylogenetic position was inferred on the basis of rbc L and SSU rRNA. Calliblepharis occidentalis was characterised mainly by the axial filament surrounded by medullary cells, weakly developed rosettes in the outer cortex and carposporophytes with central columns. Our molecular phylogeny showed that C. occidentalis is distinct from C. fimbriata ( rbc L divergence of 4.5%). Relationships among the 10 species currently assigned to Calliblepharis remain unresolved and whether they form a monophyletic clade is uncertain. Our results suggest that this genus is composed of five morphological groups, here called Calliblepharis sensu lato, based on vegetative and reproductive features such as type of placentation in the carposporophyte, axial filament arrangement and formation of rosettes. The morphological groups might represent different genera, but this hypothesis needs to be tested with better resolved phylogenies based on more comprehensive gene datasets.